MYOCARDIAL INFARCTION: AN IN-DEPTH OVERVIEW OF CAUSES, MECHANISMS, AND CURRENT TREATMENT APPROACHES (International journal of medical sciences, 2026)
Myocardial infarction (MI), commonly known as a heart attack, occurs when there is a sustained interruption in coronary artery blood flow, resulting in permanent damage and death of cardiac muscle cells (cardiomyocytes). Even with major progress in catheter-based interventions, MI continues to be a leading cause of death worldwide and significant long-term impairment. This article examines the root causes, underlying biological processes, and up-to-date, evidence-supported treatments. Particular attention is given to drug-based regimens and strategies for prevention to enhance survival and quality of life.